Climatic Change in Nunavut - Hardy, Douglas; Bradley, Raymond (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Instrumental^ recorded climate records from Nunavut are too short to provide a useful perspective on climate variability in the region. Furthermore, there are only a few paleoclimate records from this large region, so that our understanding of pre-anthropogenic climatic changes is limited. The available proxy records suggest that the climate of the last few hundred years has ranged from one of the coldest episodes of the post-glacial, toone of the warmest periods. Additional high-resolution records are needed, and a case is made for obtaining well-calibrated paleoclimate data from laminated lake sediments in the region.